(untitled) - Kyokai, Kenkokunenjigiyo (Tokyo, 1936)
This book is published mainly for the purpose of making foreigners understand Japan in society, culture, industry and sightseeing
Keywords: Industries,Công nghiệp; Japan,Nhật Bản